2014
DOI: 10.1016/j.ecoenv.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth elements in intertidal sediments of Bohai Bay, China: Concentration, fractionation and the influence of sediment texture

Abstract: a b s t r a c tSurface sediments from intertidal Bohai Bay were assessed using a four-step sequential extraction procedure to determine their concentrations of rare earth elements (REEs) and the chemical forms in which those elements were present. The normalized ratios La/Gd and La/Yb showed that LREE contents were not significantly higher than the middle REEs or HREE contents. A negative Ce anomaly and positive Eu were observed in sand and silty sand sediments, whereas no significant Ce or Eu anomaly was foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…The dCe in our present study are quite in line with those of the Changjiang River (1.00), Huanghe River (1.00), Po River (1.00) (Yang et al, 2002;Kramer et al, 2002) and the intertidal zone of the Bohai Bay reported in our early study (Zhang et al, 2014). Hoyle et al (1984) suggested that Ce behaved coherently with its neighboring elements as a result of estuarine mixing so that Ce anomaly is not generated in estuary.…”
Section: Normalization Analysissupporting
confidence: 79%
See 3 more Smart Citations
“…The dCe in our present study are quite in line with those of the Changjiang River (1.00), Huanghe River (1.00), Po River (1.00) (Yang et al, 2002;Kramer et al, 2002) and the intertidal zone of the Bohai Bay reported in our early study (Zhang et al, 2014). Hoyle et al (1984) suggested that Ce behaved coherently with its neighboring elements as a result of estuarine mixing so that Ce anomaly is not generated in estuary.…”
Section: Normalization Analysissupporting
confidence: 79%
“…These results showed that the sampled area was not heavily Zhang et al (2014), probably due to their similar material source and sedimentary environment evolution. In surface sediments from the coastal Bohai Bay, the normalized concentration ratios of La/Gd and La/Yb were lower than 1.00 except at DLJ-2 and DLJ-3 (both were 1.03) (Fig.…”
Section: Normalization Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…Indeed, they are known for their high affinity for fine grain size fractions in soils or sediments (Cullers et al, 1975;Ramesh et al, 2000;Caetano et al, 2013;Bayon et al, 2015), and also for their association with several chemical fractions (Zhang et al, 1998;Gu et al, 2001;Aubert et al, 2004;Davranche et al, 2008). Carbonates, iron oxides, and organic matter are thought to be among the more important controlling factors of REE (Leybourne and Johannesson, 2008;Zhang et al, 2014). The grain size, mineralogy, and carbonate content of sediments could thus contribute to the significant differences in the distribution and fractionation of REE (Yang et al, 2002;Feng, 2010;Suja et al, 2017).…”
Section: Introductionmentioning
confidence: 99%